The Role of PAI Teachers in Facilitating Students' Spiritual Development Through Hadrah Extracurricular Activities at SMK PGRI 5 Jember - Marto, Roy; Mukhsin, Mukhsin (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study aims to determine the role of Islamic Education teachers in facilitating students' spiritual development through hadrah extracurricular activities at SMK PGRI 5 Jember. The background of this study is the decline in moral values among teenagers. This study uses field research with a descriptive qualitative approach. The main subjects are Islamic Education teachers. Observation, interviews, and documentation were used as tools for data collection. Data analysis was conducted using descriptive analysis. The results of the study indicate that in developing students' spirituality, PAI teachers at SMK PGRI 5 Jember utilize the hadrah extracurricular activity as a supplementary learning tool for students. The approach taken by PAI teachers is quite effective, such as mentoring, planning, facilitating, and serving as role models to provide real learning to make it easier for students to understand spiritual values and attitudes based on direct experience.